'HIV and work don't go together': Employment as a social determinant of HIV outcomes among men who have sex with men and transgender women in the Dominican Republic. Issue 12 (2nd December 2017) - Barrington, Clare; Acevedo, Ramon; Donastorg, Yeycy; Perez, Martha; Kerrigan, Deanna
ABSTRACT: Men who have sex with men (MSM) and transgender women are disproportionately affected by HIV in the Dominican Republic. Little is known about their experiences living with HIV as a chronic condition. We explored employment as a social determinant of well-being with HIV. We conducted 42 qualitative in-depth interviews with MSM ( n = 16) and transgender women ( n = 5) living with HIV; each participant completed 2 interviews to facilitate depth and iterative analysis. We used narrative analysis and systematic coding to identify salient themes related to employment and the HIV experience and developed a conceptual model of the pathways between HIV stigma, unemployment, and HIV outcomes. Early life experiences, including rejection from families and school, resulted in limited work opportunities, especially among transgender women. Following HIV diagnosis, participants across all socio-economic levels lost jobs and/or were unable to get jobs due to illegal HIV testing and HIV stigma and discrimination. Not being able to work impacted mental health, engagement in HIV care, and overall well-being. We conclude that lack of employment is a salient concern among MSM and transgender women living with HIV. Holistic, multi-level programmes that address illegal HIV testing and discriminatory hiring practices are urgently needed to facilitate engagement in care and long-term well-being.